Comprehensive Review of Emerging Missile Propulsion Technologies - Ma Conghui, Shen Xin, Qin Fei, Sun Zhenhua (Hangkong bingqi)
Power system is a core factor influencing the performance of tactical missile. As conventional propulsion system, solid-rocket engine, turbojet engine, and sub-sonic combustion ramjet engines have become increasingly mature, and the technological progress has been slow. Scramjet engines and detonation engines, which are in line with the faster and farther goals of missile, have subversive significance in the field of missile power technology. They have become research hotspots in recent years and supported the research and development of related missile. This paper summarizes the basic principles and research status of scramjet engines and detonation engines. From the perspective of missile applications, the technical advantages and difficulties of the above two types of engine are analyzed, providing reference for in-depth research and application of related propulsion technologies.